Person, Process, Choice: The Psychology of New Venture Creation - Shaver, Kelly G.; Scott, Linda R. (Entrepreneurship Theory and Practice, 1992)
Psychology can be distinguished from other behavioral sciences by its emphasis on the behavior of the individual person. Behavior, in turn, is influenced by the way in which the external world is represented in the mind, and by the individual's exercise of choice. The article examines the possibility that relatively enduring attributes of the person might affect entrepreneurial activity, describes the social cognitive processes Involved in constructing representations of the external environment, and suggests which motivational variables affect behavioral choices. Although past research on “the psychology of the entrepreneur” has not been productive, a psychological approach based on persons, process, and choice holds promise for the future.